THE INFLUENCE OF AUDIT COMMITTEE AND OWNERSHIP STRUCTURE ON EARNINGS MANAGEMENT - Kusumaningtyas, Metta; Farida, Dessy Noor (Jurnal Dinamika Akuntansi, 2016)
The objective of this study is to analyze the influence of audit committee characteristics and ownership structure on earnings management. The characteristics which are used to measure the effectiveness of the audit committee are audit committee independence, audit committee competency, audit committee activity and audit committee size. Ownership structures are characteristics of public ownership, institutional ownership, and managerial ownership. Earnings management in this study were measured by using the value of discretionary accrual. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2007-2012. Based on purposive sampling method, the number of samples in this study was 66 samples. Testing the hypothesis used multiple regression analysis. The results indicate that audit committee independent, audit committee size and institutional ownership had a significant negative effect on earnings management. Instead the others variables such as audit committee competency, audit committee activity, public ownership and managerial ownership did not influenced on earnings management.